Mating Systems of the Tree-Killing Bark Beetle Polygraphus proximus (Coleoptera: Curculionidae: Scolytinae). Issue 6 (25th December 2020) - Köbayashi, Kenta; Takagi, Etsuro
Abstract: Polygraphus proximus Blandford (Coleoptera: Curculionidae: Scolytinae) has caused mass mortality of fir ( Abies spp. (Pinaceae)) forests across large areas of Russia in the past decade. More recently, mass mortality of  A . veitchii  Lindl. due to P . proximus infestation has been reported in Japan. This bark beetle species traditionally has been considered to be polygynous because their galleries have multiple gallery arms, and because harem-polygyny is common in the tribe Polygraphini. Although the mating system(s) potentially could have a marked effect on their reproductive success and population dynamics, the reproductive behavior of the tree-killing bark beetle P . proximus has not been investigated in detail in a natural setting in Japan. We, therefore, investigated the number of males and females in a gallery and the number of gallery arms in Abies species in Japan. None of the galleries examined contained more than one male, and 57.2% of the galleries had multiple gallery arms, even though only 2.8% of the galleries contained two females. The findings showed that the typical mating system employed by P . proximus is monogyny and that this species constructs multiple gallery arms in each gallery. In addition, 70.4% of galleries in which the sex of adult beetles could be determined contained no males, and 26.6% contained no females, suggesting that P . proximus males and females re-emerge.